PENERAPAN MEDIA PEMBELAJARAN PAPAN STATISTIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI STATISTIKA DIKELAS XII IPA 1 SMA NEGERI 1 RAO - Afifah Azmi Nst; Aulia Safitri Lubis; Diyah Hoiriyah (Jurnal Cermatika, 2024)
Student learning outcomes are still low due to the low ability of teachers to utilize learning media in the learning process. This makes it increasingly difficult for students to understand the material presented by the teacher, because they become less active and pay less attention to the teacher's explanation of the material presented. This research formulates the question of whether the use of statistics whiteboard media in statistics teaching materials at SMA Negeri 1 Rao Class XII IPA 1 SMA Negeri 1 Rao in mathematics education can improve student learning outcomes. The approach used in this research is classroom action research (PTK) using the Kurt Lewin model which consists of the stages of planning, taking action, observing and reflecting. The subjects of this research were students of Class XII Science 1 SMA Negeri 1 Rao. The data collection tools used are observation to observe student activities and teacher tests to measure student learning outcomes, interviews to collect data, and data collection on statistical board media.